(untitled) (UNIZIK Journal of Educational Management and Policy, 2026)
The study investigated the opportunities and challenges of integrating artificial intelligence (AI) in managing security in secondary schools in Anambra State. Two research questions guided the study while two hypotheses were tested at the 0.05 significance level. A descriptive survey design was adopted. The population comprised 267 principals of public secondary schools in Anambra State, consisting of 159 males and 108 females. The entire population was studied. Data were collected using a validated self-structured questionnaire. Reliability was determined using Cronbach Alpha, yielding coefficients of 0.88 and 0.89 for Clusters 1 and 2, with an overall coefficient of 0.89. Mean, standard deviation and t-test were employed for data analysis. Findings revealed that AI integration offers opportunities such as real-time monitoring, predictive analysis and minimised human error in surveillance. Major challenges identified include high implementation costs, inadequate technical expertise, resistance to technology adoption, poor infrastructure and insufficient personnel training. Results further indicated a significant gender difference in principals’ views on AI opportunities. The study concluded that AI provides substantial prospects for improving security management in secondary schools in Anambra State. It recommended increased government investment in security infrastructure to support AI-driven surveillance and protection systems.